USE OF MALE STERILITY AND SYNTHESIS OF MAINTAINER LINE FOR HYBRID SEED PRODUCTION IN ONION (Allium cepa L.) (Bangladesh Journal of Plant Breeding and Genetics, 2016)
Field experiment was carried out and one cytoplasmic genetic male sterile line (Smsms) and two local lines were identified as maintainer lines (Fmsms). These two crossed materials namely 3(Shallot*Local) and 4 (Shallot *Local) produced 100 per cent male sterile progeny in full sib and backcross generations. The Shallot * market cultivar produced both male fertile and male sterile segregating progenies. It indicated that the market material is probably determined by dominant and recessive independently acting genes which genetically impure lines. All other crossed materials produced 100 per cent male fertile progeny upon crossing with shallot. So, in backcross generations, the male sterile plants were more when local was used as recurrent parent. Thus, the local cultivar can be used as maintainer line for Shallot. The performance of 904 F1 and 905 F1 hybrids over check and better parent was found to be preferably better using CMS system. So, considering the genetics and stability of the male sterility mechanism, further studies are needed towards hybrid variety development in Bangladesh.